of Social Support on Self-Regulated Learning in Sarmag program Students - Lintang Retno Winayu; Praesti Sedjo; Mimi Wahyuni (Journal Research of Social Science, Economics, and Management, 2022)
Social support is the existence of interpersonal interactions that are shown by providing assistance to other individuals, where the assistance is generally obtained from people who are meaningful to the individual concerned. In addition, social support also affects self-regulated learning which involves peer support, family support, facility support, information support and emotional support. Aspects of social support that affect self-regulated learning are emotional support, reward support, instrumental support, information support and social network support. The characteristics possessed by self-regulated learning are individuals who have the ability to be active in regulating their learning activities in various ways. The environment around the individual such as the family environment, community environment, academic environment, and group environment have an influence on individual success in learning. This study aims to see the effect of social support on self-regulated learning in Sarmag program students with a total of 121 students as respondents. The sampling method used an accidental sampling technique, while the data collection technique used a questionnaire. Hypothesis testing using simple regression analysis, which shows that there is a very significant effect of social support on self-regulated learning in Sarmag program students with an F value of 30.323 with a significance value of 0.000 (P < 0.05) and an R square value of 0.203 which indicates The effect of self-regulated learning which is very significant on social support is 20.3% with the remaining 79.7% influenced by other factors, namely self-efficacy, motivation, Intelligence Quotient.